Inventory of Medicinal Plants in the Home Gardens of the Residents of Negeri Latu, Amalatu Subdistrict, West Seram Regency - Abdul M Ukratalo; Ahmad Ramdani Patty; Suraya Manuputty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The inventory of medicinal plants involves collecting and organizing data regarding natural resources for resource management planning and serving as a database to reveal the potential of plants in a given area. This study aims to inventory the types of medicinal plants found in the home gardens of the residents of Negeri Latu, Amalatu District, West Seram Regency. The data collection methods employed were exploration and descriptive surveys. The gathered data was subsequently analyzed to identify the benefits or uses of the plants based on relevant literature. The results indicate that 57 species of medicinal plants were found in the home gardens of the residents of Negeri Latu. These plants possess various properties, including antidiabetic, antimalarial, anti-inflammatory, antioxidant, anticholesterol, anticancer, antidysentery, analgesic, antipyretic, and mosquito-repellent effects. This finding highlights the significant potential of home gardens in Negeri Latu as a rich natural resource of medicinal plants. The diversity of plant species reflects the local traditional knowledge of utilizing flora as a natural solution to various health issues.